Prenatal testing in pregnancies conceived by in vitro fertilization with pre‐implantation genetic testing. (20th May 2020) - Arian, Sara E.; Erfani, Hadi; Westerfield, Lauren E.; Buffie, Alexandra; Nassef, Salma; Gibbons, William E.; Van den Veyver, Ignatia B.
Abstract: Objective: Women with pregnancies resulting from in vitro fertilization (IVF) with normal pre‐implantation genetic testing for aneuploidy (PGT‐A) are advised to undergo prenatal screening and testing during pregnancy. It is not well known how many follow these recommendations. Our objective was to study prenatal testing decisions made by women with pregnancies conceived through IVF with PGT‐A. Methods: We performed a retrospective review of women who received genetic counseling during pregnancies conceived through IVF with normal PGT‐A. We excluded those who received genetic counseling preconceptionally prior to IVF. Statistical analysis included descriptive statistics and after testing for normality by the Kolmogorov‐Smirnov test, independent t test, Mann‐Whitney U test, or Chi‐square/Fisher's exact test. Results: Data from 83 women were included. Of these, 53 (63.9%) had at least one of the following prenatal tests: first trimester combined screening (16.9%), non‐invasive prenatal screening (NIPS) (45.8%), second trimester serum screening (6%), and invasive diagnostic testing (6%). 10.8% had more than one of the above tests and 36.1% declined all tests. Conclusion: Almost two‐thirds of women who were pregnant after IVF with normal PGT‐A had prenatal aneuploidy screening or testing. Future prospective studies with larger cohorts are needed to further ascertain decision making in this population.